A review of genus Nysius Dallas in Argentina (Hemiptera: Heteroptera: Orsillidae) - Pall, José Luis; Kihn, Romina Gisela; Diez, Fernando (Zootaxa, 2016)
The orsillid genus Nysius Dallas is a complex and large genus with more than 100 described species worldwide, and includes many species of agricultural importance, one such example is N. simulans (Stål) from Argentina. Three species of Nysius are found in this country: N. simulans (Stål), N. irroratus (Spinola) and N. puberulus Berg. The material available for the present study, consisting of over 610 specimens, was collected by sweep-net, G-Vac and light trap in the provinces of Chubut (42° to 46°S; 63.5° to 72° W), La Pampa (35º to 39º south; 63º to 68º West), Neuquén (36° to 41° S; 68° to 71°W) and Río Negro (37° to 42°S; 62° to 71°W), in the central region of Argentina, during the years 2010–2014. Although the species N. simulans is frequently recorded as a pest of soybean crop, there exist no detailed description but only a brief general diagnosis. In the present contribution, therefore, we provide a detailed redescription as well as an updated distribution of N. simulans and N. irroratus, and a key for species of genus Nysius present in Argentina.